PENGEMBANGAN PROGRAM BERITA INFOTAINMENT TV NASIONAL BERDASARKAN PREFERENSI MASYARAKAT MENGGUNAKAN ANALISIS KONJOIN - DAMEYANTI, PUTRI; SUSILAWATI, MADE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2020)
Current technological advances cause information to be obtained quickly. Such information can be obtained through printed media or electronic media. Television is included in the category of electronic media. The infotainment program is one of the television programs. Almost all television stations have infotainment programs running every day. This proves that people love the infotainment program, so the infotainment program still running until now. People’s as watchers/audiens of the infotainment program have the right to provide an assessment of the quality of infotainment programs related to satisfaction and preference to assist in the development of infotainment programs. To understand people's preferences for infotainment programs, it can be done using conjoint analysis. In this research, it was found that the attributes that influence the people’s in watching infotainment program are presenter, air time, and program duration. In general, the infotainment program that desired by the people was an infotainment program that has a paired presenter, running at night with a half hour run time